Influence of the region and the sap flow of orange trees on the population dynamics of Aonidiella aurantii (Hemiptera: Diaspididae) in Mitidja (Algeria) - AROUA, Khaoula (ENTOMOLOGIA HELLENICA, 2024)
The objective of this work is to study the influence of the region and the sap thrust on some bioecological aspects of the red scale Aonidiella aurantii (Maskell) (Hemiptera: Coccomorpha: Diaspididae). The monitoring of the life cycle of A. aurantii has been conducted by periodic counting of populations on different parts of the tree such as branches and leaves during two consecutive years (2017 and 2018) in the region of Rouiba [36°44′00′′N; 3°17′00′′E] and Oued El Alleug [36°44′00′′N; 3°17′00′′E]. The study of population dynamics shows that the armored scale develops three annual generations on the orange tree in the regions of Rouiba and Oued Alleug, which also coincide with the three flushes of sap: spring, summer and autumn. The spring period also remains the most favorable for its development. In addition, it has a very marked affinity for the center orientation and the branches of the tree, which offer it the optimal conditions for its development. As for the previous species, the shift observed in the temporal distribution depends essentially on the region (distance from the sea) but also on the triggering of sap surges. In fact, it was determined that the three periods of activity in Oued Alleug began a little later compared to those in Rouïba. In autumn and winter, the crawlers of the red scale insect are more abundant in the center of the tree while in spring and summer they shelter in the east of the tree where the climatic conditions are more favorable. The average values of fecundity varied from 1 to 20 crawlers/female in Rouïba, while in Oued Alleug, from 0 to 19 crawlers/female. The analysis of variance reveals that the factor year, month and region induce a very highly significant difference (p<0.0001) in the two years in the region of Rouïba and Oued Alleug with a probability of (p<0.0001). The distribution of neonate larvae was a good indicator for understanding the red scale insect behavior. The findings of this study have huge implications for A. aurantii control of red scale. Key words: sap thrust, orange tree, Rouiba, Oued Alleug